Financial Performance Mediation On Corporate Governance Towards Company Value Of Issuers Listed In The LQ45 Index - Kurniawan, Andrie; Sofyanty, Devi; Givan, Bryan (Jurnal Multidisiplin Sahombu, 2025)
This study examines the relationship between corporate governance, financial performance, and company value. The research employs a quantitative approach using path analysis with AMOS 22 to test direct and indirect relationships. Data were obtained from secondary sources, specifically financial reports of companies listed in the LQ45 index on the Indonesia Stock Exchange from 2019 to 2023. The sample consists of 120 companies selected through purposive sampling based on specific criteria. The results show that board size has a significant influence on company value, while board meetings do not. Financial performance, tested as a mediating variable, does not significantly mediate the relationship between corporate governance and company value. The Sobel test confirms the absence of mediation for both board size and board meetings. The findings suggest that governance practices impact company value more through structural aspects than performance indicators. The negative relationship between board size and company value indicates potential challenges related to communication and decision-making in larger boards, aligning with prior research. These results highlight the importance of optimizing board size to enhance company value while reconsidering the effectiveness of frequent meetings. Future research is recommended to explore other mediating factors, such as strategic practices or investor perceptions, to provide a more comprehensive understanding of these relationships.